Isolation And Characterization Of Rubber-Degrading Bacteria From Aged Latex - Chia, Kim Hou (2013)
Malaysia is one of the largest rubber producing countries. Rubber waste management plays an important role to deal with high production and consumption of rubber in our country. In order to find an alternative for current rubber waste management, rubber-degrading bacteria were isolated from aged latex in Bukit Jambul hiking site, Penang. Among the 13 isolates obtained, isolate CFMR-7 showed clear zone formation around its colonies on the latex overlay agar. Morphology of CFMR-7 under phase-contrast light microscope and scanning electron microscope (SEM) showed that it is an actinomycete containing conidia. Degradation study was carried out by culturing CFMR-7 with latex glove. The dry biomass weight was increased approximately 0.1 g/L throughout the cultivation period. The surface morphology of the latex gloves was examined using SEM. It was clearly shown that surface of the latex glove cultivated with CFMR-7 for 14 days was rougher compared to that of latex glove without inocula. Besides, colonization of CFMR-7 on the latex glove was observed. The signs of enzymatic degradation further conclude that this isolate is able to degrade latex glove. The 16S rRNA gene sequence of CFMR-7 revealed that it is Streptomyces sp. Besides, the 16S rRNA gene sequence identification of two of the isolates revealed that isolates CDRG-7 and CFR-4 are 99% similar to Gordonia polyisoprenivorans and Gordonia terrae, respectively. G. polyisoprenivorans was reported to degrade rubber without clear zone formation on the latex overlay agar. Subsequently, a set of degenerate primers was designed from the conserved regions of the latex clearing protein (lcp) genes available in NCBI database. Amplification of DNA fragments from all the isolates was performed by using this set of primers.